2018
DOI: 10.1007/s00467-018-3992-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic testing in children with a clinical diagnosis of ARPKD identifies phenocopies

Abstract: We found all ARPKD cases without PKHD1 point mutations to be phenocopies, and none to be explained by biallelic PKHD1 copy number variations. Screening for copy number variations is recommended in patients with a heterozygous point mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…However, hepatic fibrosis is usually not detected prenatally and cannot be used in making the diagnosis. In cases with no detectable mutations, a thorough sequencing has identified phenocopies involving other genes in 20% of these cases . This is of utmost importance regarding prenatal diagnosis and preimplantation diagnosis for the parents' future reproductive plans and points towards the importance in performing WES/WGS when sequencing the PKD1 and PKHD1 genes fails to identify a mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, hepatic fibrosis is usually not detected prenatally and cannot be used in making the diagnosis. In cases with no detectable mutations, a thorough sequencing has identified phenocopies involving other genes in 20% of these cases . This is of utmost importance regarding prenatal diagnosis and preimplantation diagnosis for the parents' future reproductive plans and points towards the importance in performing WES/WGS when sequencing the PKD1 and PKHD1 genes fails to identify a mutation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Moreover, mutations in several other genes can produce a phenocopy of ARPKD ("see Differential Diagnosis"). 10,11 Clinical Course…”
Section: Etiology and Prevalencementioning
confidence: 99%
“…Variants are often novel and unique to single families in "nonisolated" populations. 11,15,[36][37][38][39] In ARPKD, genotype-phenotype correlations depend on types of mutations. The most severely affected patients typically have two truncating mutations, while patients with milder phenotype have two missense or a missense and a truncating change.…”
Section: Other Clinical Aspectsmentioning
confidence: 99%
“…Finally, several phenocopies exist that can lead to a misdiagnosis of ARPKD. A recent study of 36 unrelated patients originally diagnosed with ARPKD but without an identified mutation in PKHD1 found that 22% harbored mutations in other genes including PKD1, HNF1b, NPHP1, TMEM67, and PKD1/TSC2) [45].…”
Section: Genetics-arpkdmentioning
confidence: 99%